Mediação da aprendizagem colaborativa na EaD : percepções de tutores a distância - Soeira, Elaine dos Reis (2013)
Considering the expansion of distance education via the Internet in Brazil and the creation of the post of tutor distance, as a professional responsible for monitoring the development of activities for students in virtual learning environments, we highlight certain concerns, among which the gap between concept of mentoring in institutions and the teaching profession, increasing the precariousness of teaching. To understand how teaching is an element in construction practices in mentoring the distance, was developed in this research, addressed to tutors from various institutions in the country, with a specific focus for the mediation of collaborative learning. In order to understand the perceptions of tutors on their practice as a way to understand how teaching is structured, there was a qualitative research, based on social representations theory, using the techniques of questionnaire and interview collect the data. The main conclusions were: among the tutors there is a consensus regarding their role as mediators, most tutors know the methodology demonstrates the collaborative learning, however there are institutions that do not value this approach and lack training for your suitable job; there are institutions that understand the practices of mentoring as a teaching activity, there is evidence that the distance tutors are undertaking actions that strengthen your practice like teaching. As an extension of the research, believes that it is important to pursue research on the teaching practices of mentoring at a distance, even as a way of strengthening the professionalization and also how to develop effective methodologies for the learning process in distance education.